Cost-effectiveness analysis of alternative colon cancer screening strategies in the context of the French national screening program. (September 2020) - Barré, Stéphanie; Leleu, Henri; Benamouzig, R.; Saurin, Jean-Christophe; Vimont, Alexandre; Taleb, Sabrine; De Bels, Frédéric
Background: A nationwide colorectal cancer (CRC) screening program was set up in France from 2009 for average-risk, asymptomatic people aged 50–74 years based on an immunochemical fecal occult blood test [faecal immunochemical test (FIT)] every 2 years, followed by colonoscopy if positive. The European standard recommends a participation rate of 45% for the program to be cost-effective, yet the latest published rate in France was 34%. The objective of this study was to compare the cost effectiveness of screening alternatives taking real-world participation rates into account. Methods: Eight screening strategies were compared, based either on a screening test (Guaiac or FIT testing, blood-based, stool DNA, computed tomography colonography, colon capsules, and sigmoidoscopy) followed by full colonoscopy if positive or direct colonoscopy. A microsimulation model was used to estimate the cost effectiveness associated with each strategy. Results: Compared with no screening, FIT was associated with a 14.0 quality-adjusted life year (QALY) increase of €50, 520 per 1000 individuals, giving an incremental cost-effectiveness ratio (ICER) of €3600/QALY. Only stool DNA and blood-based testing were associated with a QALY increase compared with FIT, with stool DNA weakly dominated by blood-based testing, and the latter associated with an ICER of €154, 600/QALY compared with FIT. All other strategies were dominated by FIT. Conclusion: FIT every 2 years appears to be the most cost-effective CRC screening strategy when taking into account a real-world participation rate of 34%.